PENINGKATAN HASIL BELAJAR MENGGUNAKAN MODEL PBL BERBANTUAN MEDIA PERMAINAN ULTADU (ULAR TANGGA DADU) PADA MATERI DIAGRAM BATANG KELAS 4 - Evina Happy Prasetyo, Rhisma; Delawanti Chrisyarani, Denna; Tumijan; Sukowati, Indah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Although bar chart learning should involve students actively, the cognitive learning outcomes of fourth-grade students at SDN Pisangcandi 2 Malang City are still low. In the pre-cycle, only 25% of students achieved KKTP 78. The study aims to improve the learning outcomes of bar chart material through the application of the PBL model assisted by the Snakes and Ladders Dice game media. The study used the Classroom Action Research method on 28 fourth-grade students. Cycle I consisted of 2 meetings, Cycle II consisted of 1 meeting. Data collection used evaluation tests and observations. Data analysis used quantitative descriptive. The results of the study increased from 25% in the pre-cycle to 54% in Cycle I Meeting 1, 79% in Cycle I Meeting 2, 89% in Cycle II. The average class value increased from pre-cycle 47 to 63 in cycle 1 meeting 1, 82 in cycle 1 meeting 2 and 90 in cycle 2. The PBL model assisted by the ULTADU game media was proven to improve student learning outcomes.